Implementation of The Advanced Encryption Standard (AES) Algorithm for Digital Image Security - Angga Aditya Permana; Luigi Ajeng Pratiwi (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2022)
Nowadays, technological advances have made it increasingly easy to obtain information, especially image data (digital images). Digital image is an interesting thing to look for information. So that misuse of data can be done for personal or public interests. Misuse of data can be avoided by adding data security systems. Cryptography is the science of securing data. Cryptography can be done using the AES (Advanced Encryption Standard) algorithm, which is an algorithm that utilizes symmetric keys. Testing is done by entering the same key in the encryption and decryption process. Encryption is the process of encoding plaintext (original text) into ciphertext (text that has been encoded). While decryption is the process of recovering the plaintext from the ciphertext. Therefore, data security is an important thing to do. This study aims to find out how encryption and decryption on the AES algorithm can be used to secure digital data. The results of this study indicate that the encryption and decryption process on the AES algorithm was successfully carried out so that it can be used to secure data on digital images.